Analisis Metode Pengukuran Kualitas Perangkat Lunak: Sebuah Tinjauan Literatur Sistematis - Ahmad Farisi; Dafid, Dafid; Rizani Teguh (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
This research is a systematic literature review that analyzes software quality measurement methods used in some researches over the last 5 years. There are many software quality measurement methods such as Boehm, ServQual, FURPS, WebQual, ISO 9126, Delone & McLean, ISO 25010, SQL-OSS, ISO 25022, and McCall. This research finds out systematically about what methods have been used to measure software quality in the last 5 years, what types of software that are being measured, and what methods are considered best practice in measuring software quality. This research found 12 articles that used several methods such as the ISO/IEC 25010:2011 Model, Function Analysis, Metric Function Oriented, and McCall. Most research applies the McCall method in measuring software quality with the web-based information system software in the education sector as the research object. Therefore, the McCall method is considered best practice in measuring software quality. The McCall method measures software quality comprehensively in product revision aspects, product transition aspects, and product operation aspects.